1995
DOI: 10.1165/ajrcmb.13.3.7654386
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary alveolar proteinosis in SCID mice.

Abstract: Pulmonary alveolar proteinosis (PAP) is an uncommon disorder of unknown origin in which the alveoli are filled with lipoproteinaceous material, including surfactant. We have characterized a spontaneously occurring lesion in the lungs of CB.17 scid/scid mice which resembles PAP in humans. Lungs from 45 severe combined immunodeficient (SCID) mice were evaluated by light and electron microscopy and immunohistochemistry. Lung lavage fluid was evaluated biochemically and for the presence of surfactant protein A (SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…37 One showed the development of secondary PAP in scid/scid mice, presumably recapitulating secondary PAP patients with immunodeficiency, although the mechanism has not yet been identified. 38 In the present model, it is clearly indicated that secondary PAP developed under aberrant T-cell activation by T-bet with monocytosis. On the basis of this finding, we suggest that T-bet-overexpressing T cells act to initiate the pathogenesis of secondary PAP.…”
Section: Discussionmentioning
confidence: 51%
“…37 One showed the development of secondary PAP in scid/scid mice, presumably recapitulating secondary PAP patients with immunodeficiency, although the mechanism has not yet been identified. 38 In the present model, it is clearly indicated that secondary PAP developed under aberrant T-cell activation by T-bet with monocytosis. On the basis of this finding, we suggest that T-bet-overexpressing T cells act to initiate the pathogenesis of secondary PAP.…”
Section: Discussionmentioning
confidence: 51%
“…Animal models of increased surfactant phospholipid and increased SP pool sizes include silica and mineral dust exposure (4), the severe-combined immunodeficient mouse (16), gene-targeted disruption of the GM-CSF or GM-CSF receptor ␤/C gene (13,26), and overexpression of IL-4 (10). Increased surfactant phospholipid in SP-D(Ϫ/Ϫ) mice was not associated with increased amounts of SPs, distinguishing this phenotype from the alveolar lipoproteinosis syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Rats exposed to inhaled silica develop PAP [90] although the mechanism was not determined. PAP also develops in mice with severe combined immunodeficiency, again without determination of the mechanism involved [91]. A recent study reported that use of dichloromethylene diphosphonic acid-encapsulated liposomes to reduce alveolar macrophage numbers increased pulmonary surfactant levels [92].…”
Section: Pathogenesis Of Secondary Papmentioning
confidence: 99%